Genetic homogeneity of Anopheles maculatus in Indonesia and origin of a novel species present in Central Java - Triwibowo Ambar Garjito; Umi Widiastuti; Mujiyono Mujiyono; Mega Tyas Prihatin; Widiarti Widiarti; Riyani Setyaningsih; Siti Alfiah; Barandi Sapta Widartono; Din Syafruddin; Tri Baskoro Tunggul Satoto; Laurent Gavotte; Michael J. Bangs; et al. (Parasites & Vectors, 2019)
Abstract Background Anopheles maculatus (s.s.) is an important vector of malaria in Indonesia. Previously it was considered the only member of the Maculatus Group present in Indonesia. A novel species was recently identified in the Kulon Progo District in Central Java. Until recently, few investigations have been conducted looking at An. maculatus genetic diversity in Indonesia, including allopatric island populations. Methods Indonesian An. maculatus (s.l.) samples were collected in several locations in Java, Lesser Sunda Island group, Sumatra and in Kulon Progo (Yogyakarta, central Java) where a novel species has been identified. Samples from a 30-year-old colony of the Kulon Progo population were also included in the analysis. Maximum-likelihood analysis established the phylogenies of the ITS2 (nuclear) and cox1 (mitochondrial) markers. Putative times of separation were based on cox1 genetic distances. Results Two species of the Maculatus Group are present in Indonesia. The novel sibling species is more closely related to Anopheles dispar than to An. maculatus (s.s.). Anopheles maculatus (s.s.) samples are homogeneous based on the ITS2 sequences. Indonesian samples and An. dispar belong to the same cox1 maternal lineage and differ from all other known members of the Maculatus Group. Divergence time between the different populations found in Java was estimated using an established cox1 mutation rate. Conclusions A novel species within the Maculatus Group, most closely related to An. dispar, is confirmed present in the Kulon Progo area of Central Java. The divergence of this species from An. maculatus (s.s.) is explained by the stable refugia in the Kulon Progo area during the quaternary period of intense volcanic activity throughout most of Java. This novel species awaits detailed morphological description before applying a formal species name. For the interim, it is proposed that the Kulon Progo population be designated An. maculatus var. menoreh to distinguish it from An. maculatus (s.s.).